2017
DOI: 10.1093/annonc/mdx171
|View full text |Cite
|
Sign up to set email alerts
|

Foods and beverages and colorectal cancer risk: a systematic review and meta-analysis of cohort studies, an update of the evidence of the WCRF-AICR Continuous Update Project

Abstract: Our results reinforce the evidence that high intake of red and processed meat and alcohol increase the risk of colorectal cancer. Milk and whole grains may have a protective role against colorectal cancer. The evidence for vegetables and fish was less convincing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
295
8
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 337 publications
(348 citation statements)
references
References 112 publications
14
295
8
3
Order By: Relevance
“…Cancer chemoprevention could yield significant reductions in cancer morbidity and mortality and disease burdens only by delaying the process of cancer development and progression a few years in the elderly [6]. Intake of beverages, fruits and vegetables in routine diets was reported to be associated with reduced cancer risk [7]. In addition, some traditional medicines (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer chemoprevention could yield significant reductions in cancer morbidity and mortality and disease burdens only by delaying the process of cancer development and progression a few years in the elderly [6]. Intake of beverages, fruits and vegetables in routine diets was reported to be associated with reduced cancer risk [7]. In addition, some traditional medicines (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…There are various potential explanations for the association between Barrett's esophagus and colorectal polyps. Although the mechanisms remain unclear, patients with Barrett's esophagus are more likely to have some of the same risk factors as patients with colorectal polyps, including older age, male sex, alcohol drinking, smoking, and obesity . In the present study, the patients with colorectal polyps had risk factors including older age, male sex, obesity, smoking, and alcohol drinking, which overlap the risk factors for Barrett's esophagus.…”
Section: Discussionmentioning
confidence: 56%
“…During recent decades, the incidence of colorectal cancer has rapidly increased in Japan . Previous studies have shown that several demographic and lifestyle‐related factors, including older age, male sex, alcohol drinking, smoking, obesity, and high intake of red and/or processed meat, increase the risk of colorectal cancers and colorectal polyps …”
Section: Introductionmentioning
confidence: 99%
“…Subsequent publications have confirmed these findings. For example, a meta-analysis as part of the World Cancer Research Fund International Continuous Update Project (WCRF-CUP) confirmed a positive doseresponse between intake of processed meat and colorectal cancer risk with an overall 12% increased risk of colorectal cancer for each 100 g/day increase of processed meat intake, although there was large variation found (95% CI = 4-21%) and a high degree of heterogeneity between study findings (I2=70%, p heterogeneity <0.01) [2]. One of the proposed mechanisms whereby processed meat can increase colorectal cancer is the formation of N-nitrosamines (NOC), which result from the reaction between a nitrosating agent, originating from nitrate (NO3)/nitrite (NO2) or smoke and a secondary amine, derived from protein [3].…”
Section: Processed Meat and Colorectal Cancermentioning
confidence: 94%